The Effect of Self- Efficacy on Student Confidence in the Use of Artificial Intelligence for Islamic Education Management - Diah Ayu Puspita Sari; Ilham Muhammad Fajar; Niksah Uma (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2025)
This study aims to analyze the effect of self-efficacy on student confidence in utilizing Artificial intelligence (AI) for Islamic education management. This quantitative research involved 63 students of the Islamic Education Management class 2020 as samples, using a Likert scale questionnaire with 30 statements. Data analysis was conducted using SPSS 25 through descriptive, prerequisite, and simple regression tests. The results showed that self-efficacy significantly affected student self-confidence, contributing to 63.2%, while other variables influenced the rest. The Kolmogorov-Smirnov normality test shows the data is normally distributed (sig. 0.071), while the simple linear regression test shows the regression model is significant (F count 25.029; sig. 0.000). This research aims to explore the application of artificial intelligence (AI) in Islamic education, particularly in teaching religious values and improving the efficiency of education management in the digital era. The results of this study are expected to provide insights into how AI can address challenges in Islamic education and introduce new approaches that are more inclusive, relevant and in line with the latest technological trends.